2010
DOI: 10.1002/elan.201000359
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Simultaneous Quantification of Nanomolar Level of Cd and Zn by Cathodic Adsorptive Stripping Voltammetry in Some Real Samples

Abstract: A novel, simple and sensitive adsorptive stripping voltammetry method was developed for simultaneous determination of Cd and Zn using N-Nitrozo-N-phenylhydroxylamine (Cupferron) as a selective complexing agent. Cadmium and zinc metals gave peaks that were distinctly separated by 450-1200 mV, allowing their determination over a wide range of concentrations. The influence of pH and the nature of supporting electrolytes, concentration of ligand, preconcentration time and applied potential were investigated. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Also, the effect of scan rate on the electrochemical signal of D 4 showed that till 100 mVs −1 , the response is increasing. It was shown that at scan rates from 0.1 to 100 mVs −1 , the dependence of redox response upon the scan rate was linear which demonstrate an adsorption controlled process [24,26]. The results of this study show that the cathodic and anodic peak current was increased with increasing the scan rate which indicates the oxidation and reduction process of D 4 at Cit-Fe 3 O 4 -DMG-CPE electrode.…”
Section: Effect Of Supporting Electrolyte Ph Deposing Timeand Potentimentioning
confidence: 52%
“…Also, the effect of scan rate on the electrochemical signal of D 4 showed that till 100 mVs −1 , the response is increasing. It was shown that at scan rates from 0.1 to 100 mVs −1 , the dependence of redox response upon the scan rate was linear which demonstrate an adsorption controlled process [24,26]. The results of this study show that the cathodic and anodic peak current was increased with increasing the scan rate which indicates the oxidation and reduction process of D 4 at Cit-Fe 3 O 4 -DMG-CPE electrode.…”
Section: Effect Of Supporting Electrolyte Ph Deposing Timeand Potentimentioning
confidence: 52%
“…This substance may be used in determination of Al(III) , U(VI) , Mo(VI) , Cd(II) , Zn(II) , Cr(VI) , Ti(IV) , Pb(II) , Ga(III) , Bi(III) , In(III) , and Cu(II) . Simultaneous determination of Bi(III) and Cd(II) , Bi(III) and Pb(II) , Cd(II) and Zn(II) , Pb(II) and V(V) , U(VI), Cd(II), and Pb(II) is possible.…”
Section: Introductioncontrasting
confidence: 59%
“…Cupferron is widely used in analytical chemistry as a complexing agent which binds to metal cations through two oxygen atoms, forming five-membered chelate rings [29,30]. Also in AdSV cupferron was used to develop sensitive procedures of trace determination of such metals as titanium [31][32][33], vanadium [34], chromium [35][36][37][38], molybdenum and copper [39], uranium [40][41][42][43], bismuth [44], europium [45], aluminium [46][47][48], cadmium and zinc [49,50]. The application of cupferron in this work for voltammetric Pb(II) determination enables low detection limit and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%